The implementation of forward chaining and certainty factor methods to examine the covid-19 vaccination eligibility - Herlina, Herlina; Yosephi, Valensa; Hazriani, Hazriani (ILKOM Jurnal Ilmiah, 2021)
Screening for the COVID-19 vaccination is an important and mandatory step to ensure the eligibility status of each candidate for vaccination. The main obstacle experienced was the ineffective screening process (a long process) that resulted in the accumulation of patients. Sometimes it takes one to two hours from registration to receiving the vaccination paper. This situation certainly causes discomfort for both participants and vaccinators. Therefore, the presence of an expert system is needed to overcome these obstacles. The expert system plays a role in simplifying service flow and shortening service time. This article discusses the application of the Forward Chaining method to formulate screening parameters so that they can be used to accurately determine vaccination eligibility. Based on the results of interviews with experts (expert doctors who handle vaccination), 12 rules were obtained from the formulation of 20 historical parameters, which will then serve as a knowledge base for the Covid-19 vaccination screening expert system. The test is carried out by comparing the results of expert screening diagnoses with an expert system using 15 samples of test data. The test results using the Certainty Factor method show that the confidence level is 84% to 99%.